The Role of One's Education and Training on the Quality of Public Services - Tirton Nefianto (Publikasi Indonesia, 2022)
This study aims to determine the role of education and training that is followed by a person on the quality of service he provides. The approach used in this research is a qualitative method. Data collection techniques used in this study were interviews, observation and documentation related to the role of education and training on the quality of public services. Triangulation method is used to validate research data with sources by cross-checking the data obtained. Based on the results of research, education and training are often a reference for someone to improve their standard of living. but there are indicators that have not gone according to community expectations, namely regarding the expertise of employees in using service aids. Among the shortcomings, there are indicators that have been achieved, namely responding, quickly, precisely, carefully, on time and responding to complaints from service users that have been carried out, this is in accordance with the wishes of the community. This study underscores the importance of continuity between education and training and the quality of services provided.